PENDEKATAN THEOSENTRIS DALAM MENANGANI KONFLIK JEMAAT:: TELAAH EKSPOSITORI SURAT 1 KORINTUS 1:10-17 DAN IMPLIKASINYA BAGI KEHIDUPAN GEREJA MASA KINI - Silalahi, Binsar Pandapotan; Tampubolon, Rolan Edwar (STT-RAI Batam, 2025)
Conflict within the church community is a historical reality that has existed since the early church, as depicted in 1 Corinthians 1:10-17. In the context of the modern church, conflict resolution is often approached pragmatically, emphasizing interpersonal techniques. Previous studies have not thoroughly examined the rhetorical structure and theological dimensions of 1 Corinthians 1:10-17 within an expository framework that centers God as the primary subject of church unity restoration. This article offers a theocentric approach as a new contribution that places God at the center of church unity. The purpose of this study is to examine 1 Corinthians 1:10-17 through exposition to formulate a paradigm for resolving contemporary church conflicts. Using a qualitative method through expository text analysis based on literature review, the results show that Paul's argumentative structure progressively affirms that church reconciliation can only occur if it is rooted in God's authority and initiative in the cross of Christ.